1988
DOI: 10.1152/jappl.1988.65.2.570
|View full text |Cite
|
Sign up to set email alerts
|

Short-term entrainment of ventilation to the walking cycle in humans

Abstract: We describe a breath-by-breath method to test for entrainment of breathing and walking cycles. Thirty-eight normal subjects walked comfortably on a treadmill while breathing through a pneumotachograph. We analyzed the time intervals between heel strikes and the onset of inspiration (or expiration) for evidence of phase locking between steps and breaths, using Monte Carlo simulation to model the probability that n consecutive inspirations (or expirations) would begin at a constant time interval +/- 0.10 s from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…Although the majority of authors searching for a kind of co-ordination or coupling between exercise rhythm and rhythm of breathing found some relationship (e.g. Bechbache & Duffin, 1977; Jasinskas, Wilson & Hoare, 1980;Bramble & Carrier, 1983;Paterson, Wood, Morton & Henstridge, 1986;Paterson, Wood, Marshall, Morton & Harrison, 1987;Hill, Adams, Parker & Rochester, 1988), there are also reports that breathing and exercise rhythms are independent (Kelman & Watson, 1973;Kay, Petersen & Vejby-Christensen, 1975). The variety of the results may be explained by differences in experimental design, in the type of exercise and other experimental conditions and methods of evaluation which in turn make a quantitative comparison between the different studies more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of authors searching for a kind of co-ordination or coupling between exercise rhythm and rhythm of breathing found some relationship (e.g. Bechbache & Duffin, 1977; Jasinskas, Wilson & Hoare, 1980;Bramble & Carrier, 1983;Paterson, Wood, Morton & Henstridge, 1986;Paterson, Wood, Marshall, Morton & Harrison, 1987;Hill, Adams, Parker & Rochester, 1988), there are also reports that breathing and exercise rhythms are independent (Kelman & Watson, 1973;Kay, Petersen & Vejby-Christensen, 1975). The variety of the results may be explained by differences in experimental design, in the type of exercise and other experimental conditions and methods of evaluation which in turn make a quantitative comparison between the different studies more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Research on humans while running has shown that entraining breathing frequency to stride rate improves running economy (Bernasconi & Kohl, 1993;Bonsignore et al, 1998;Bramble & Carrier, 1983), possibly by improving the economy of ventilation by reducing the metabolic cost of breathing (Bramble & Carrier, 1983;Heinrich, 2001;Hill et al, 1988;Paterson et al, 1986).…”
Section: Rationalementioning
confidence: 99%
“…Entrainment has also been shown to occur, sometimes infrequently or transiently, in humans while walking and running (Bechbache & Duffin, 1977;Bernasconi & Kohl, 1993;Berry et al, 1988;Bonsignore et al, 1998;Bramble & Carrier, 1983;Hill et al, 1988;McDermott et al, 2003;Paterson et al, 1987;Raßler & Kohl, 1996;Takano, 1995), cycling (Bechbache & Duffin, 1977;Bernasconi & Kohl, 1993;Bonsignore et al, 1998;Jasinskas et al, 1980;Paterson et al, 1986), rowing (Mahler et al, 1991), and even while walking with crutches (Hurst et al, 2001) ( Table 1). Animals that run on four legs seem to be constrained to a 1:1 ratio between steps and breaths, especially as speed increases (Boggs, 2002;Lafortuna et al, 1996;Simons, 1999 (Bramble & Carrier, 1983).…”
Section: Definitions Of Termsmentioning
confidence: 99%
See 2 more Smart Citations